Russian urban and challenges of modernity: neural networks in digital city discourse - L. R. Mirkushina (Современная наука и инновации)
In the context of the adaptation of domestic urbanism to current trends in development, science, technology and society, the prospects of the Smart City project are explored, where sustainable development and increasing the comfort of human life optimize economic processes. The actor-network theory has become relevant in the study of the city as a ―living network‖, where not only a person is an active reality modifier, but also things, and in our case, neural network technologies set trends in urban discourse and change the nature of relationships.